Koliščarska naselbina Stare gmajne in njen čas = Stare gmajne Pile-dwelling Settlement and Its Era Ljubljansko barje v 2. polovici 4. tisočletja pr. Kr. = The Ljubljansko barje in the 2nd half of the 4th millennium BC - Velušček, Anton (Opera Instituti Archaeologici Sloveniae, 2009)
The third publication in which an international group of researchers, under management of collaborators of the Institute of Archaeology at the Scientific Research Centre of the Slovenian Academy of Sciences and Arts (ZRC SAZU) from Ljubljana, studies problems of pile-dwelling inhabitation of the Ljubljansko barje, introduces results of researches performed at pile-dwelling settlements Stare gmajne, Blatna Brezovica and Veliki Otavnik Ib, i.e. settlements dating to the 2nd half of the 4th millennium BC.